2015
DOI: 10.5037/jomr.2015.6303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dentofacial Deformity on Quality of Life: Age and Gender Differences Evaluated Through OQLQ, OHIP and SF36

Abstract: ObjectivesThe aim of this study was to verify the impact of dentofacial deformity on quality of life and explore gender and age differences.Material and MethodsThe impact of dentofacial deformity (DD) on quality of life was evaluated through questionnaires; Short Form Health Survey (SF36), Oral Health Impact Profile Questionnaire (OHIP), Orthognathic Quality of Life Questionnaire (OQLQ) and a single question answered by a Visual Analogue Scale.ResultsSignificant differences between male and female patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
5
17
1
1
Order By: Relevance
“…These results are similar to other published studies (Hunt et al 2001;Soh and Narayanan 2013). Of note is the fact that this reduced QoL was more pronounced in females than males in relation to all aspects except dentofacial appearance; other recently published studies have found similar gender disparities (Bortoluzzi et al 2015;Palomares et al 2016;Stagles et al 2016). Comparison of the pre-treatment patients with the 2-year postsurgery group in the current study revealed a strong effect of treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to other published studies (Hunt et al 2001;Soh and Narayanan 2013). Of note is the fact that this reduced QoL was more pronounced in females than males in relation to all aspects except dentofacial appearance; other recently published studies have found similar gender disparities (Bortoluzzi et al 2015;Palomares et al 2016;Stagles et al 2016). Comparison of the pre-treatment patients with the 2-year postsurgery group in the current study revealed a strong effect of treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Two-way ANOVAS (treatment stage by gender) were carried out for each of the outcomes on the OQLQ measure; the factor of gender being entered since it has previously been reported as influencing QoL (Bortoluzzi et al 2015). Repeat of these analyses was performed with age added as a co-variate as a weak effect has also previously been evidenced (Bortoluzzi et al 2015), but this was not found to change the findings. The ANOVA for the total score of the OQLQ showed significant treatment stage by gender-interactive effects and this is graphically displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are controversies related to the impact of facial deformity on the individual's OHRQoL. Some studies are unanimous in recognizing the negative impact (Guimarães et al 2014;Bortoluzzi et al, 2015;Kilinc & Ertas 2015); others affirm that dental esthetics has a direct influence on the OHRQoL, irrespective of the facial deformity (Guimarães et al 2014;Isiekwe et al 2016). It is known that individuals with severe malocclusion have a greater negative impact on oral health than the general population, directly affecting the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the impact of OHRQoL, the Oral Health Impact Profile (OHIP-14) is recognized as one of the most valid and reliable instruments (Montero & Gómez-Polo 2017). Furthermore, when the domains that comprise the OHIP-14 are evaluated separately, physical pain is the one that shows the highest impact on the quality of life of patients with a facial deformity (Lee et al 2008;Bortoluzzi et al, 2015;Bortoluzzi et al 2017) and is, therefore, an important aspect of evaluating in the diagnosis and treatment plan (Torres et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Un puntaje OQLQ total puede variar de 0 a 88. Una puntuación más alta indica una calidad de vida más pobre y una puntuación inferior indica mejor calidad de vida posoperatoria (9,10) .…”
Section: Introductionunclassified